Dental care for HIV-positive patients in the Unified Health System: a systematic review (Research, Society and Development, 2022)
One of the most stigmatized diseases by society is the Human Immunodeficiency Virus (HIV) and the Acquired Immunodeficiency Syndrome (AIDS). As there is still no cure and the treatment is indeterminate, the effects that these diseases cause in patients over time are much discussed. Although it suffers enormous resistance and prejudice, treatment and preventive measures in Brazil can be done through the Unified Health System. Therefore, the present study aimed to present a theoretical framework regarding the treatment of HIV carried out by the SUS. Subsequently, the dental professional's approach to these patients in the SUS was discussed. In the methodology, a systematic review of the literature was carried out, based on the periodic databases, PubMed, LILACS and Scielo, whose temporal cut was between the years 2017 to 2021. In the results, the dental professional in this context, becomes essential in the period of treatment, being able to work together with the patient in order to remove him from the prejudice that these diseases bring. Added to this, the importance of having educational measures for these professionals, both with regard to primary care and the issue of biosafety and self-care.